The factors influencing suicide attempts among adolescents: A review article - Mohammad-Rafi Bazrafshan; Hamed Delam (Shiraz University of Medical Sciences, 2020)
Background: Suicide and Suicidal attempt at the 1996 World Health Organization Summit was an important public health and anti-social behavioral issue. Suicide rates are one of the most important indicators of the community's mental health. The present study was designed to elucidate the factors affecting suicidal attempts among adolescents. Methods: This is  a review study. Two researchers searched for suicide-related articles and related factors between October and November 2019 at five Latin scientific databases (Google Scholar, PubMed / Medline, Scopus, ISI Web of Science and Embase). Results: The most important factors in suicidal attempts in adolescents included individual factors, family factors, and social factors. Hormonal changes in puberty in adolescents, especially in girls, can affect the adolescents' behavior. The breakdown of the family structure can have negative consequences for children and cause them to commit suicidal attempts. Conclusion: The available evidence indicates the influence of individual, family, and social factors at the beginning of the process of suicidal attempt among adolescents. Therefore, by focusing on preventing risk factors leading to suicidal behavior in adolescents, teaching how to deal with stress and increasing the adolescents' access to specialized counseling services and useful social networks, a suitable support system can be provided for these people.